Cadmium exposure induces TNF-α-mediated necroptosis via FPR2/TGF-β/NF-κB pathway in swine myocardium. (15th April 2021) - Zhao, Xia; Wang, Shengchen; Li, Xiaojing; Liu, Honggui; Xu, Shiwen
Graphical abstract: Highlights: Cd exposure leads to necroptosis in swine myocardium. Cd exposure regulates FPR2/TGF-β/NF-κB pathway in swine myocardium. Cd exposure reduces swine myocardium antioxidant capacity by inhibiting Nrf2 pathway. Abstract: Cadmium (Cd) is one common environmental pollutant with systemic toxicity. Lipoxin A4 (LXA4) can regulate transforming growth factor-β (TGF-β) pathway and alleviate tissue injury via binding to formyl peptide receptor 2 (FPR2). The activation of nuclear factor-κB (NF-κB) pathway can promote the occurence of necroptosis. However, whether Cd exposure induces necroptosis in swine myocardium and the role of FPR2/TGF-β/NF-κB pathway in this process are unclear. Hence, we established Cd-exposed swine myocardial injury model by feeding a CdCl2 added diet (20 mg Cd/kg diet). Hematoxylin-eosin (H&E) staining was used to observe the morphological changes, and inductively coupled plasma mass spectrometry (ICP-MS) was performed to detect the levels of ion elements in myocardium. We further detected LXA4 and its receptor FPR2, TGF-β, Nrf2, NF-κB pathway and necroptosis related-genes expressions by RT-PCR and western blot. The results showed that Cd exposure induced necrotic cell death and ion homeostasis imbalance in swine myocardium. Moreover, Cd exposure increased the LXA4 content, inhibited the FPR2 expression, activated TGF-β pathway and suppressed Nrf2 pathway, activating the NF-κB pathway. In addition, Cd exposure increased the expressions of necroptosis related-genes TNF-α, TNFR1, RIP1, RIP3 and MLKL. It indicated Cd exposure induced necroptosis via FPR2/TGF-β/NF-κB pathway, revealing the potential mechanism of Cd-induced cardiotoxicity in swine myocardium.